2019
DOI: 10.1007/s15010-019-01287-5
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory syncytial virus contributes to more severe respiratory morbidity than influenza in children < 2 years during seasonal influenza peaks

Abstract: Purpose To compare the frequency and the severity of influenza and respiratory syncytial viruses (RSV) infections among children < 24 months hospitalized with respiratory symptoms. Methods Data from a prospective study conducted during the peak of five influenza seasons in the Province of Quebec, Canada were used. Results We detected higher frequency of RSV compared to influenza viruses (55.3% vs. 16.3%). Radiologically confirmed pneumonia was significantly more frequent in children with RSV (39%) than those w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 17 publications
1
14
0
Order By: Relevance
“…Highest rates were detected in young ones and in those born before or at the beginning of the RSV season. Previous studies also reported the same findings 6,20,25–29 . RSV‐associated hospitalization risk in infants born at the end of RSV season (January to March) appeared to be lower than the ones born between August and September.…”
Section: Discussionsupporting
confidence: 73%
“…Highest rates were detected in young ones and in those born before or at the beginning of the RSV season. Previous studies also reported the same findings 6,20,25–29 . RSV‐associated hospitalization risk in infants born at the end of RSV season (January to March) appeared to be lower than the ones born between August and September.…”
Section: Discussionsupporting
confidence: 73%
“…Even multicenter studies find that in children under 6 months the prevalence is 50% and in children under 2 years of age 88%, a fact that corroborates the high burden of RSV in children < 2 years, especially in infants < 6 months [ 50 , 51 ]. The younger the age, the greater the risk of RSV infection, as corroborated by several authors, indicating a greater risk especially in children between 3 to 5 months [ 48 , 52 , 53 ], although other studies point out that RSV-associated hospitalizations reach their maximum peak in children under 3 months [ 54 ]. Other authors suggest a higher percentage of infection in children 0 to 12 months of age [ 45 , 54 , 55 , 56 , 57 , 58 ].…”
Section: Discussionmentioning
confidence: 84%
“…This is particularly relevant for children younger than 24 months of age, as severe courses of RSV infection are observed at this age. In fact, Amini et al showed that RSV infections were significantly more severe than Influenza infections in hospitalized children < 3 month [ 8 ]. In our tertiary care pediatric center, the rise in viral respiratory infections lead to an increase in hospitalizations due to viral pneumonia with RSV and Rhinovirus being the main triggers [ 9 ].…”
Section: Discussionmentioning
confidence: 99%